2007
DOI: 10.1007/bf03325209
|View full text |Cite
|
Sign up to set email alerts
|

Low systolic blood pressure is associated with impaired cognitive function in the oldest old: longitudinal observations in a population-based sample 80 years and older

Abstract: Lower SBP in the oldest old is associated with an increased risk of cognitive impairment even after adjustment for compromised vitality. In late life, the risk of cognitive decline needs to be considered in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
4
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(89 citation statements)
references
References 31 publications
3
79
4
3
Order By: Relevance
“…This is clinically relevant, as cognitive decline is common among patients with type 2 diabetes and may influence management [8]. Our data do not support commonly held views [8,15,16] suggesting general restraints with regard to cardiovascular risk management in patients with cognitive impairment. Therefore, rather than denying patients with type 2 diabetes risk-modifying treatment on the basis of cognitive dysfunction, such patients deserve a similar careful balancing of all potential risks and benefits associated with treatment to that of patients with intact cognitive function.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…This is clinically relevant, as cognitive decline is common among patients with type 2 diabetes and may influence management [8]. Our data do not support commonly held views [8,15,16] suggesting general restraints with regard to cardiovascular risk management in patients with cognitive impairment. Therefore, rather than denying patients with type 2 diabetes risk-modifying treatment on the basis of cognitive dysfunction, such patients deserve a similar careful balancing of all potential risks and benefits associated with treatment to that of patients with intact cognitive function.…”
Section: Discussioncontrasting
confidence: 72%
“…In the absence of clear cardiovascular benefits, such treatments may be used cautiously or even withheld in these patients due to concerns that lower cerebral blood flow or incident hypoglycaemia may exacerbate cognitive decline and even provoke the onset of dementia [8,15,16]. The recent Action in Diabetes and Vascular Disease: Preterax and Diamicron Modified Release Controlled Evaluation (ADVANCE) study, investigated the separate effects of both routine BP lowering and intensive glucose control on vascular outcomes in a broad range of patients with type 2 diabetes [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…However, a Cochrane review [38] found no evidence of association between blood pressure-lowering treatments and the risk of developing dementia or cognitive impairment and we have not found studies reporting a risk associated with heightened diastolic blood pressure when other relevant variables were controlled. In addition, in the oldest-old, it was found that higher systolic blood pressure was associated with better cognition [39] and in another longitudinal study investigating the relationship between blood pressure and late-life cognitive change, no linear association was found between systolic or diastolic blood pressure and cognition but a curvilinear relationship between diastolic blood pressure and cognition was present, showing an association between both high and low diastolic blood pressure and decreased cognition [40] . It may be that blood pressure medication and/or lower diastolic blood pressure in some individuals lead to chronic cerebral hypoperfusion/hypoxia [41] which over time might lead to neurodegeneration and negatively impact on cognition.…”
Section: Discussionmentioning
confidence: 99%
“…Hypotension and the risk of dementia Several longitudinal studies have also identified low BP as a risk factor for the development of AD and dementia [Nilsson et al 2007;Verghese et al 2003;Ruitenberg et al 2001;Morris et al 2001] (Table 3). The Bronx Aging Study [Verghese et al 2003] followed an elderly nondemented cohort (!…”
Section: Midlife Hypertension and The Risk Of Dementiamentioning
confidence: 99%